Performance analysis of a transcritical N 2 O refrigeration cycle with vortex tube - Jain G.; Arora A.; Gupta S.N. (My University, 2025)
In the present study, vortex tube is used in transcritical vapour compression cycle as expansion device to improve the coefficient of performance (COP). The thermodynamic analysis has been performed using nitrous oxide in transcritical cycle with vortex tube (TCVT) and its results are compared with those of a transcritical cycle with expansion valve (TCEV). The evaporator and the gas cooler temperatures have been varied between −55°C and 5°C and between 35°C and 60°C, respectively, for the analysis. The COP of the TCVT improves by 1.72–27.01% compared to TCEV.  A decrease in evaporator temperature and an increase in gas cooler exit temperature result in a decrease in COP. The increase in cold mass fraction brings a negligible increase in maximum COP. The performance comparison of N 2 O and CO 2 in TCVT shows that maximum cooling COP for N 2 O is higher than for CO 2 , but the optimum pressure required for N 2 O is lower than for CO 2 . © 2017, © 2017 Informa UK Limited, trading as Taylor & Francis Group.